A review of the reporting of web searching to identify studies for Cochrane systematic reviews. (9th November 2017) - Briscoe, Simon
Abstract : The literature searches that are used to identify studies for inclusion in a systematic review should be comprehensively reported. This ensures that the literature searches are transparent and reproducible, which is important for assessing the strengths and weaknesses of a systematic review and re‐running the literature searches when conducting an update review. Web searching using search engines and the websites of topically relevant organisations is sometimes used as a supplementary literature search method. Previous research has shown that the reporting of web searching in systematic reviews often lacks important details and is thus not transparent or reproducible. Useful details to report about web searching include the name of the search engine or website, the URL, the date searched, the search strategy, and the number of results. This study reviews the reporting of web searching to identify studies for Cochrane systematic reviews published in the 6‐month period August 2016 to January 2017 ( n = 423). Of these reviews, 61 reviews reported using web searching using a search engine or website as a literature search method. In the majority of reviews, the reporting of web searching was found to lack essential detail for ensuring transparency and reproducibility, such as the search terms. Recommendations are made on how to improve the reporting of web searching in Cochrane systematic reviews.